Faktor-Faktor yang Mempengaruh Siswa SLTA dalam Memilih Perguruan Tinggi di Kabupaten Batang Hari (Studi Kasus Pada STAI dan STIE-GK Muara Bulian) - Ahmad Fithoni; Atang Priyatna (Universitas Batanghari Jambi, 2019)
This study aims to find out and analyze the factors that influence the decision of high school students in choosing universities in Batang Hari Regency. The object of research is STAI and STIE-GK Muara Bulian. This research is descriptive quantitative with the number of respondents as many as 75 students for each college which is the object of research registered in the 2018/2019 academic year. This type of research is descriptive qualitative research that aims to determine whether there is an influence or relationship between two or more variables with the analysis tools used include Partial Test (t test), Simultaneous Test (Test F), and Determination Coefficient Test (R2). The results of the study show that the independent variables include Study Program variables (X1), Accreditation Status (X2), Facilities (X3) and Costs (X4) on Student Decisions (Y). For STAI Muara Bulian, only Accreditation variables have a partial influence on student decisions and even then it is not significant. For STIE-GK Muara Bulian, it is known that all independent variables have a partial and significant influence on the decisions of high school students to enter. Judging from the F test, it is known that the independent variables simultaneously have an influence on the dependent variable in having a college in Batang Hari Regency. The test results of the coefficient of determination for STAI Muara Bulian amounted to 88.9% and for STIE-GK Muara Bulian at 95.3% while the remaining respectively 11.1% and 4.7% were influenced by other factors not included in the research variable.